Kriteria Pertanggungjawaban dan Sistem Peradilan Pidana bagi Pelaku Tindak Pidana Pengancaman Mahasiswa di Media Sosial dalam Putusan Nomor : 172/PID.SUS/2019/PN.JKT.SEL - Ni Made Purnawati; Akhmad Munawar; Hanafi (Jurnal Hukum Lex Generalis, 2024)
The aim of this research is to determine the factors that influenced the judge's decision in the case of criminal threats on social media in Decision Number: 172 / PID.SUS / 2019 / PN.JKT.SEL against children as sexual abuse perpetrators in South Jakarta City to analyze and analyze the decision. The statutory and case approaches are two examples of the normative research methodology that is employed. The information was gathered from theses, journals, legislation, and literature. In this study, data management and analysis were done in a deductive manner. According to the study's findings, the court continues to violate the proportionality principle while imposing a sentence on the offender. The judge's decision is then influenced by a number of factors, such as: 1. Elements that come from the judge. 2. Elements that come from the accused.